Analisis Penerapan Teori Belajar Konstruktivisme Pada Buku Matematika Kelas 5 Kurikulum 2013 Revisi Terbitan Erlangga - Setiyani Setiyani; Wiena Safitri; Alfi Satria (BADAN PENERBIT STIEPARI PRESS, 2024)
This study examines the application of constructivism learning theory in fifth-grade mathematics. Constructivism emphasizes that students build knowledge through their own experiences via active, gradual engagement, where the teacher acts as a facilitator rather than a knowledge transmitter. Mathematics, essential for everyday life, should offer meaningful lessons that relate to real-world experiences. The constructivist approach consists of stages such as perception, exploration, discussion and explanation of concepts, and the development and application of concepts. The study aims to analyze the supporting media in the fifth-grade mathematics book, curriculum 2013 revision published by Erlangga, and assess its alignment with the constructivist learning stages. This qualitative study uses a library research approach, with the primary data sourced from the mathematics book and secondary data from relevant journals and studies. Data was collected through documentation, using a marking sheet to evaluate the book's compatibility with the constructivism stages. The results indicate that the book supports constructivist learning, providing media like pictures and videos accessible via QR codes. The book's content aligns well with the constructivist learning stages, with a 97.5% compliance rate, falling into the